Effect of the GaN:Mg Contact Layer on the Light‐Output and Current‐Voltage Characteristic of UVB LEDs. Issue 10 (11th December 2017) - Susilo, Norman; Enslin, Johannes; Sulmoni, Luca; Guttmann, Martin; Zeimer, Ute; Wernicke, Tim; Weyers, Markus; Kneissl, Michael
Abstract : In order to realize UVB LEDs with high wall‐plug efficiencies, the light extraction efficiency from the LED heterostructure must be maximized and operating voltages reduced. In this study, we investigate the effect of the GaN:Mg contact layer thickness on the light‐output and current‐voltage characteristics of UVB LEDs. AlGaN‐based LED heterostructures, that are fully transparent for UVB emission except for the GaN:Mg contact layer are grown by metal organic vapor phase epitaxy on c‐plane sapphire substrates. From transfer line measurements, it is found that the p‐contact resistivity increases rapidly with decreasing GaN:Mg thickness and exhibits a pronounced Schottky behavior for layer thicknesses below 40 nm. At the same time, the emission power increases from 0.1 to 1.5 mW at 20 mA with decreasing GaN:Mg thickness. Ray tracing simulations of the light extraction efficiency of the UVB LEDs show that absorption in the GaN:Mg layer leads to lower emission powers for thicker GaN:Mg layers. Furthermore, with increasing GaN:Mg thickness additional losses occur due to a decrease of the internal quantum efficiency. The electro‐optical and the structural properties of the devices show that a 40 nm thick GaN:Mg contact layer is the best compromise due to the low p‐contact resistivity (0.01 Ω cm 2 ) and at the same time still sufficient UVB‐transmission resulting in UVB LEDs with external quantum efficiencies of more than 1% and a wall plug efficiency of 0.4% (at 20 mA), measured on‐wafer. Abstract : In order to realize UVB light emitting diodes (LEDs) with high wall‐plug efficiencies, the light extraction efficiency from the LED heterostructure must be maximized and operating voltages reduced. In this study, we investigate the effect of the GaN:Mg con‐tact layer thickness on the light‐output and current‐voltage characteristics of UVB LEDs.